When the 'strong arms' leave the farm - Simelton, Elisabeth (World Agroforestry Centre, 2019)
Presented by Elisabeth Simelton (World AgroForestry Centre), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.